Decoding Multiple Antibody Positivity: Lessons from Paraneoplastic Sensory Ataxia - S Sidharth; Ayush Agarwal; Divyani Garg; Anita Mahadevan; Shamim A Shamim; Pranjal Gupta; Divya M Radhakrishnan; Awadh K Pandit; Achal K Srivastava (Annals of Indian Academy of Neurology, 2024)
Paraneoplastic neurologic syndromes are cancer-associated, immune-mediated neurologic manifestations that may involve any part of the nervous system. They usually present with characteristic neurologic features and should be considered in high-risk phenotypes such as limbic encephalitis, encephalomyelitis, rapidly progressive cerebellar syndrome, opsoclonus–myoclonus, sensory neuronopathy, enteric neuropathy, and Lambert–Eaton myasthenic syndrome. The diagnosis is made by antibody positivity in the serum or cerebrospinal fluid, in the presence of an appropriate clinical phenotype. Findings on antibody testing by immunoblot should always be verified by immunofluorescence. We report a rare case of sensory neuronopathy with triple paraneoplastic antibody positivity (anti-Hu, anti-collapsing response-mediator protein 5, and anti-amphiphysin) on immunoblot but only anti-Hu positivity on immunofluorescence. The presence of lower facial dyskinesias should raise the possibility of an immune-mediated neurologic syndrome in the appropriate clinical context.